2007
DOI: 10.1103/physrevc.75.034614
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the pairing effect using newly evaluated empirical studies for 14–15 MeV neutron reaction cross sections

Abstract: The asymmetry term effects for the cross sections of (n, charged particle) and (n, 2n) reactions at 14-15 MeV neutron incident energy have been investigated. The effects of pairing and odd-even nucleon numbers in new data and in the formula of Tel et al. [J. Phys. G. 29, 2169[J. Phys. G. 29, (2003] are discussed. We have determined three different parameters groups by the classification of nuclei into even-even, even-odd, and odd-even (n, d) reactions. In addition, since there are not enough experimental dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(7 citation statements)
references
References 30 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…The researches have shown that the fast neutron-induced reaction is possible with equilibrium (compound) process in region I (A = 40-62). But, in region III (A = 90-160), this reaction is possible with the pre-equilibrium process and in the intermediate region II (A = 63-89), the reaction is governed by both equilibrium and pre-equilibrium processes [15,19,20]. Kumabe and Fukuda have modified the Levkovskii's formula by taking this into consideration for (n, p) and (n, α) cross-sections at 14-15 MeV [15].…”
Section: Empirical and Semi-empirical Systematics For The Fast Neutromentioning
confidence: 99%
See 2 more Smart Citations
“…The researches have shown that the fast neutron-induced reaction is possible with equilibrium (compound) process in region I (A = 40-62). But, in region III (A = 90-160), this reaction is possible with the pre-equilibrium process and in the intermediate region II (A = 63-89), the reaction is governed by both equilibrium and pre-equilibrium processes [15,19,20]. Kumabe and Fukuda have modified the Levkovskii's formula by taking this into consideration for (n, p) and (n, α) cross-sections at 14-15 MeV [15].…”
Section: Empirical and Semi-empirical Systematics For The Fast Neutromentioning
confidence: 99%
“…This formula depends on the asymmetry parameter, s = (N − Z)/A, and has the pairing effect on the binding energy systematics of nuclear shell model. Tel et al also obtained a new appropriate coefficient by using this formula for (n, 2n), (n, α), (n, t) and (n, d) reactions [19][20][21][22][23][24]. Betak et al have applied this formula for (n, p) reactions and have found agreement with odd-A nucleus in the latest experiment for 112−124 Sn thin target [25].…”
Section: Empirical and Semi-empirical Systematics For The Fast Neutromentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the charged particles emitted from nuclear reactions produced by neutrons will produce serious damage to the structure materials, particularly in nuclear reactor with high neutron flux (Lishan and Yuling, 1992). It is need to accumulate new data of nuclear reaction cross sections around the incident energy of 20 MeV (Tel et al, 2007). Thereby, more many experimental investigations have been carried out to obtain and detect the neutron particles at various energy ranges.…”
Section: Introductionmentioning
confidence: 99%
“…In addition the obtained data via the different techniques are essential to develop additional nuclear theoretical calculation models to explain the reaction mechanisms and the properties of the excited nuclear states at different energy ranges. On the other hand, the experimental neutron cross sections for the nuclear reactions at projectile energies around 14-15 MeV and the emission spectra of various particles have a profound importance for understanding the binding energy systematics, nuclear structure, the particle-nucleus interactions, and refined nuclear models (Tel et al, 2007). Many measurements of the excitation curves of the reactions induced by the fast neutrons on medium and heavy mass targets are quite difficult because of the low induced activities, such as the (n,2p), (n, 2 H), (n, 3 H), (n, 3 He) cross sections, etc.…”
Section: Introductionmentioning
confidence: 99%